The Value of Women's Moral Education in the Public and Domestic: Nilai Pendidikan Akhlak Wanita di Ranah Publik dan Domestik - Ferredika, Inggit Iksan; Romadlon, Dzulfikar Akbar (Universitas Muhammadiyah Sidoarjo, 2022)
The decline in moral values ​​in modern times like today, women are more likely to follow western customs, especially in terms of dressing and following their habits. The morals of today's women are in decline. Many women who come out of their nature, do not know their true identity. This type of research uses library research, the method used is the analytical method. The approach used is a descriptive approach, which is to explain the meaning or meaning contained in the verse that comes from Tafsir Al - Azhar and analyze the meaning in secondary sources so that it can answer the existing questions. The results of the research findings show that: (1) the educational value of women contained in Surah Al Ahzab verses 28-35, namely qana'ah, not excessive in clothing or jewelry, obedient to Allah and His Messenger, dressing appropriately for women. no body shape and does not resemble a man. (2) the value of moral education in the public and domestic spheres, namely good ethics towards parents, how to use the clothes they wear, and how to talk to men who are not their relatives. With this educational value, it can be applied in the community, schools and other places, so that it is expected to become a good habit and as an example for Muslims and other Muslims.